2022
DOI: 10.1159/000526808
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact of Glucagon-Like Peptide-1 Receptor Analogs on the Complications of Obesity

Abstract: Background: Obesity is a chronic disease associated with increased morbidity and mortality due to its complications. The aims of obesity treatment are primarily to accomplish weight loss, and prevention or treatment of its complications. Lifestyle changes along with behavioral therapy constitute the first line treatment of obesity followed by pharmacotherapy. Glucagon-like peptide receptor analogs (GLP-1 RA’s) are among the approved pharmacotherapy options. Their central effect on suppressing appetite results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 144 publications
0
1
0
Order By: Relevance
“…Recent studies have shown a wide spectrum of weight reductions in different obesity-related conditions including diabetes mellitus (DM), nonalcoholic fatty liver disease, obstructive sleep apnea, etc. by different types of GLP-1-RAs [11]. Liraglutide is a once-daily injectable GLP-1-RA that has achieved the approval of the Food and Drug Administration (USA) for the management of DM and obesity [12].…”
Section: Imc Journal Of Medical Sciencementioning
confidence: 99%
“…Recent studies have shown a wide spectrum of weight reductions in different obesity-related conditions including diabetes mellitus (DM), nonalcoholic fatty liver disease, obstructive sleep apnea, etc. by different types of GLP-1-RAs [11]. Liraglutide is a once-daily injectable GLP-1-RA that has achieved the approval of the Food and Drug Administration (USA) for the management of DM and obesity [12].…”
Section: Imc Journal Of Medical Sciencementioning
confidence: 99%